Net primary productivity of soybean using different data sources and estimation methods - Rodigheri, Grazieli (Revista Ciência Agronômica, 2021)
Net primary productivity (NPP) can be used to quantify the relative role of climate and human activities invegetation dynamics. Given its importance, many NPP estimation models have been developed, but some of the required datais still limited. Therefore, this study aimed to estimate the potential and actual NPP by testing different approaches regardingthe data source and estimation methods and evaluate the human appropriation of NPP (HANPP) in a soybean field cultivatedin southern Brazil. For this, data were obtained from field-measured NPP in soybean cultivation in Carazinho, Rio Grande doSul, Brazil, and compared to the potential and actual NPP estimations using the CASA model and data from ERA-Interim.Subsequently, land use changes due to agricultural activities were evaluated from the potential and actual NPP through HANPP.No significant difference was observed associated with the used data sources, showing that the ERA-Interim reanalysis weatherdata can be employed for this purpose. The actual NPP estimations by the CASA model were consistent with a high associationwith the data measured in the field. HANPP, through only one annual soybean cultivation, represented 29% of the potential NPPin the region. It indicates the potential to increase intensification with annual crops in the region.